2003
DOI: 10.1093/geront/43.3.318
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Age on the Use of Health and Self-Care Information: Confronting the Stereotype

Abstract: We find convincing evidence to counter the stereotype that older adults are resistant to trying new health information technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
31
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…Similarly, more participants over 70 years of age reported that information about stroke and aphasia should not be provided via computer programs or Internet. This fi nding is in accordance with Wagner and Wagner 85 who found that older adults were less likely than other age groups to use computers to access health information.…”
supporting
confidence: 91%
“…Similarly, more participants over 70 years of age reported that information about stroke and aphasia should not be provided via computer programs or Internet. This fi nding is in accordance with Wagner and Wagner 85 who found that older adults were less likely than other age groups to use computers to access health information.…”
supporting
confidence: 91%
“…In contrast, the present results indicate that common everyday technology related to increased use of ICT in health care and other community services may exclude people with dementia from participation in certain aspects of society and represent a barrier to their independence and self-fulfillment. This risk for people with dementia has also been pointed out by Topo et al (2002), while in general, the elderly have been found to be willing to use the health information provided by ICT (Smith Wagner & Wagner, 2003). Our results also indicated that there is a risk that technology can provide a false sense of security to caregivers and clients, which is worth particular attention.…”
supporting
confidence: 75%
“…If avoiding going to the bank is the only perceived gain, it might not be significant enough to compensate for the trouble, especially as going to the bank may even be a positive thing as it provides exercise and social contacts (also noted in [40]). Additionally, easy access to health information is often considered an important benefit that the Web could offer to older people [39]. Nevertheless, these participants were not particularly interested in accessing health-related information from the Web because they either did not have any severe problems with their health or they wanted to consult their physician on those issues.…”
Section: Motivation Behind Learning To Use Computersmentioning
confidence: 99%